PENERAPAN RUTINITAS PEMBACAAN DZIKIR RATIB AL-HADDAD SEBAGAI SARANA PEMBENTUKAN PSIKOSPIRITUAL SISWA DI SMKI NURUL HIJRIYAH SEJATI CAMPLONG SAMPANG - jaini, jai; Suwantoro (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study investigates the implementation of the daily recitation of Ratib al-Haddadas a means of developing students' psychospiritual character at SMKI Nurul Hijriyah Sejati, Camplong, Sampang. The research was conducted using a qualitative descriptive approach through observation, interviews, and documentation. The purpose of the study is to describe how the structured practice of Ratib al-Haddadcontributes to the emotional, spiritual, and behavioral development of students in a formal Islamic educational setting. The findings reveal that the daily dzikirroutine, held every morning before lessons begin, significantly influences students' mental calmness, emotional control, and spiritual discipline. Students demonstrate increased focus, a deeper sense of religious awareness, and more stable psychological behavior throughout the learning process. The practice, which involves reading the Ratibtext collectively with guidance from teachers and staff, has successfully shaped a religious culture within the school environment. In addition, the program contributes to internalizing Islamic values, such as gratitude, patience, and sincerity, while also building communal bonds among students. Despite minor challenges in comprehension and participation levels, the program has proven to be an effective model for character education rooted in Islamic spirituality. This routine serves as an integrative approach that harmonizes spiritual tradition with modern education, making it worthy of adoption in other Islamic institutions.